Factors affecting migration of Filipino special education teachers to the United States - Lazaro, Elizabeth R. (2007)
The continuing increase in migration has become a threat to the country's teaching force. This is a descriptive study that identified the reasons why SPED teachers leave the country to teach in the US. Thirthy-six Filipino SPED teachers who were based in Maryland and also in Washington D.C. Area participated in the study. The results of the study showed that these teachers who migrated are mostly from the ages 23-40, married, from Luzon provinces, had higher educational attainment and are likely to be females. Monetary factors and non monetary factors such as reward and recognition, educational opportunities, better working conditions, independence and reunion with family, that affected their decision to migrate were determined. Stakeholders for this study are the SPED teachers who opt to stay in the country, the future SPED teacher migrants, and institutions that train future SPED teachers.